1998
DOI: 10.1143/jjap.37.l703
|View full text |Cite
|
Sign up to set email alerts
|

Terminating Structure of Plasma-Assisted Molecular Beam Epitaxial GaN{0001} Film Surface Identified by Coaxial Impact Collision Ion Scattering Spectroscopy

Abstract: Terminating structures of the GaN{0001} films grown on nitrided sapphire(0001) substrates by plasma-assisted molecular beam epitaxy (MBE) have been investigated by coaxial impact collision ion scattering spectroscopy (CAICISS). The analyses of incidence angle dependences of time of flight (TOF) spectra have shown that the surfaces of GaN films grown under both N-rich and Ga-rich conditions are (0001) N-planes terminated with Ga atoms. This implies that (0001), N-terminated surfaces of GaN films grown under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…However, this model does not agree with the existing experimental and theoretical data in the literature. Smith et al [1,2] have suggested that GaN is terminated with a Ga adlayer and recent experimental measurements using CAICISS [9] suggest that both N and Ga polarity surfaces are terminated with Ga atoms. An alternative growth model, which is consistent with this background and also consistent with our RHEED data is outlined in model B.…”
Section: Possible Growth Modelsmentioning
confidence: 99%
“…However, this model does not agree with the existing experimental and theoretical data in the literature. Smith et al [1,2] have suggested that GaN is terminated with a Ga adlayer and recent experimental measurements using CAICISS [9] suggest that both N and Ga polarity surfaces are terminated with Ga atoms. An alternative growth model, which is consistent with this background and also consistent with our RHEED data is outlined in model B.…”
Section: Possible Growth Modelsmentioning
confidence: 99%
“…CAICISS has proven to be useful in exploring surfaces and subsurface structures [14][15][16][17][18][19][20][21]. It has been revealed that Fe(1 1 1) thin films with a bcc-type structure can be epitaxially grown on a Si(1 1 1) crystal even at room temperature (RT) and form a single-domain structure.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, columnar structures were observed in the AFM image of RF-MBE-grown heteroepitaxial GaN layers. It has been reported that the morphology is greatly affected by the lattice polarity at the beginning of the growth [9,10]. In this case, it is likely that the lattice polarity will be changed by the different kinds of substrates.…”
Section: Resultsmentioning
confidence: 99%